2014
DOI: 10.2355/isijinternational.54.2025
|View full text |Cite
|
Sign up to set email alerts
|

Viscosities of Iron Blast Furnace Slags

Abstract: The viscosities of the industrial and synthetic iron blast furnace slags have been measured using a custom designed rotating bob apparatus. This advanced apparatus enables control of the gas atmosphere and rapid quenching of the samples on completion of the viscosity measurements. The experiments were carried out using Mo spindle and crucible under ultra-high purity Ar flow. The microstructures and phase compositions of the quenched slag samples were determined by Electron Probe X-ray Microanalysis (EPMA) afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 26 publications
1
20
0
1
Order By: Relevance
“…As a result, the viscosity values for the two types of viscometers are lower than those in the work of Kim et al 27) The viscosity values reported by Han 25) were collected from the other publications and contain no information about the procedure of viscosity measurement. Meanwhile, the significant deviation from the results of Tang et al 29) and Chen et al 34) can be associated with the considerable differences in the slag compositions as well as the measurement techniques. In these two mentioned researches, Brookfield digital viscometers were applied and the viscosity of slags was estimated with an approx.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…As a result, the viscosity values for the two types of viscometers are lower than those in the work of Kim et al 27) The viscosity values reported by Han 25) were collected from the other publications and contain no information about the procedure of viscosity measurement. Meanwhile, the significant deviation from the results of Tang et al 29) and Chen et al 34) can be associated with the considerable differences in the slag compositions as well as the measurement techniques. In these two mentioned researches, Brookfield digital viscometers were applied and the viscosity of slags was estimated with an approx.…”
Section: Resultsmentioning
confidence: 79%
“…As previously noted, the equilibrium state of the slag viscosity during the continuous cooling may not be achieved which can cause the incompatibility of the different results. Besides, Chen et al 34) reported data for a slag that contains 17.3 mass% of Al 2 O 3 . This high concentration of aluminum oxide in slag can lead to the increase of viscosity as reported by Persson et al 8) and Yan et al…”
Section: Resultsmentioning
confidence: 99%
“…3assumes that the free energy of the ternary system and the quasi-binary system are identical, since these systems have the same composition despite being expressed differently. Equations (4) and (5) are based on the partition law in the cell model. They are suitable for a binary system (or quasi-binary system, such as the case herein), but are applicable only if the composition of system and the number of cells are known.…”
Section: Correlation Equations Between Equivalent Circuitmentioning
confidence: 99%
“…Molten oxides such as silicate melts are used in various fields, including metal manufacturing 1) and radioactive waste treatment. 2) However, the rheological properties of the melt affect the quality of the manufactured products; moreover, the physical properties of the melt-such as the viscosity, [3][4][5] thermal conductivity, 6,7) density, [8][9][10] and surface tension 11,12) -are affected by its chemical composition, crystallization, and structure. Numerous studies into the physical and structural properties of melts have therefore been carried out.…”
Section: Introductionmentioning
confidence: 99%
“…Machin et al [30][31][32][33] Scarfe et al 51) Forsbacka et al 60) Saito et al 61) Lee et al 62) Shankar et al 63) Kim et al 64) Song et al 65) Tang et al 66) Liao et al 67) Kim et al 52) Chen et al 68) Gao et al 69) Li et al 59) Yao et al 70) Sun et al 71) the application of the viscosity model. These three types Table 4.…”
Section: Sio2-al2o3unclassified